Assessment of Digital Awareness and Competence Among Lecturers and Students for Enhancing Social Studies Instruction in Government-Owned Universities - Omojemite, Matthew Damilola (Journal of Posthumanism, 2025)
Proper utilization of technology by students and lecturers in tertiary institutions is essential during the era of digital revolution. This study aimed to evaluate the level of digital awareness and competency of the students and lecturers in the government-owned institutions in South-West Nigeria. A descriptive survey research design was used for this study. They were all lecturers and full-time undergraduate students in the public universities of the region. Multistage sampling led to a sample of 102 lecturers and 1,507 students. The data was collected by two structured tools: the Lecturers' Preparedness for Digitalisation of Higher Education Instruction Questionnaire (LPDHEIQ) and the Students' Preparedness for Digitalisation of Higher Education Instruction Questionnaire (SPDHEIQ). Every questionnaire had six scales with demographic data, awareness of digitalisation, and digital competence and the items were scaled on a four-point Likert scale. The instruments were validated based on expert judgment in educational technology, measurement, and supervision. Pilot study application in non-sample institutions yielded Cronbach's alpha values of 0.79 for LPDHEIQ and 0.97 for SPDHEIQ, indicating high internal consistency. The questionnaires were filled online through Google Forms dispatched on social media platforms and email. Descriptive statistics such as means and standard deviations were used to respond to the research questions, and t-test statistics to test the hypothesis at a 0.05 level of significance. The findings showed lecturers to possess a moderate level of digital awareness and competence, while students yielded moderately high to high levels of digital competence. A significant difference was created between lecturers' and students' digital competence in favor of the students. Universities are recommended to place highest emphasis on continuous digital training and support frameworks to reinforce lecturers' competence and narrow the digital preparedness gap.